MOBILISASI ALSINTAN BERDASARKAN KALENDER TANAM PADA BUDIDAYA PADI DI KABUPATEN GROBOGAN, JAWA TENGAH - Trip Alihamsyah (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2016)
ABSTRACTMobilization of Agricultural Machines Based on Crop Calender for Rice Cultivation in Grobogan District, Central Java. Agricultural machines for rice production in Central Java especially Grobogan District are already intensively developed, but their utilization is still low. Optimalization use of those agricultural machines is needed to improve their performances. This research aimed: (i) To arrange mobilization concept of agriculturalmachines in order to optimize their use for rice cultivation in Grobogan District, and (ii) To analyze the deficit and working capacity of those agricultural machines after optimalization use through their mobilization. This research was focused on hand tractors and power threshers only, and was conducted in Grobogan District, in 2013. Data on lowland area and population of hand tractor and power thresher were collected from agricultural office of Grobogan District and its Sub-districts, meanwhile data dealing with agricultural machine’s performances were collected through interview with agricultural machines owner and UPJA using well structured questioners. The collected data were arranged in the form of table and map, and then analyzed using requirement and mobilization analyses. The results showed that through mobilization scenario of 20% available agricultural machines among sub-district with four different planting times in Grobogan District could improve the machine’s performance and could reduce their deficit. By mobilizing those agricultural machines for rice cultivation in Grobogan District, their deficit could be reduced up to >50%, meanwhile, working capacity of those machines could be increased from < 30 ha/year/unit before mobilization become 35,5 ha/year/unit after mobilization.Keywords: optimalization, mobilization, agricultural machines, crop calendar, rice ABSTRAKAlsintan untuk budidaya padi di Jawa Tengah khususnya di Kabupaten Grobogan sudah berkembang namun pemanfaatannya masih rendah. Mobilisasi alsintan antar wilayah berdasarkan kalender tanam diharapkan dapat meningkatkan pemanfaatannya yang sekaligus meningkatkan kinerjanya. Tujuan kajian ini adalah: (1) Menyusun konsep mobilisasi alsintan berdasarkan kalender tanam untuk optimalisasi pemanfaatannya pada budidaya padi di Kabupaten Grobogan, dan (2) Menganalisis kekurangan dan kapasitas kerja alsintan setelah dilakukan mobilisasi.Kajian ini difokuskan kepada traktor tangan dan perontok padi di Kabupaten Grobogan pada tahun 2013. Data luas lahan sawah serta penyebaran traktor tangan dan perontok padi diperoleh dari kantor Dinas Pertanian Tanaman Pangan Kabupaten dan Kecamatan, sedangkan data primer kinerja alsintan dan jasa sewanya diperoleh melalui wawancara kepada pemilik alsintan dan UPJA di tiga kecamatan yang banyak alsintannya masing-masing tiga responden menggunakan daftar pertanyaan terstruktur. Data yang diperoleh disusun dalam bentuk tabel dan peta, kemudian dianalisis menggunakan Analisis Kebutuhan Alsintan serta Analisis Mobilisasi Alsintan dan Analisis Kapasitas Kerja Alsintan. Konsep mobilisasi alsintan disusun berdasarkan perbedaan jadwal tanam menurut kalender tanam antar kecamatan. Hasil kajian menunjukkan bahwa melalui skenario mobilisasi 20% alsintan yang ada antar kecamatan dengan 4 jadwal tanam padi berbeda di kabupaten Grobogan dapat meningkatkan pemanfaatan dan kinerja alsintan serta menekan kekurangan alsintannya. Dengan skenario mobilisasi alsintan tersebut, kekurangan traktor tangan dan perontok padi di Kabupaten Grobogan dapat ditekan sampai > 50%, sedangkan kapasitas kerja alsintannya dapat ditingkatkan dari awalnya < 30 ha/tahun/unit menjadi 35,5 ha/tahun/unit setelah mobilisasi.Kata kunci: optimalisasi, mobilisasi, alsintan, kalender tanam, padi